Feeling machine for material-specific machining. Issue 1 (2020) - Bergmann, Benjamin; Witt, Matthias
Abstract: In the machining of material compounds, materials with differing properties must be identified during the process and process parameters must be controlled accordingly. Structure integrated strain gauges in feeling machines are a promising approach for providing signals for monitoring and control tasks. This paper presents the first investigation and implementation of this technology for a turning machine turret. Firstly, the simulation based positioning of the sensors is discussed. Secondly, disturbance variables such as cooling temperature and assembly tolerances of machine components, which affect the strain measurement, are investigated. Finally, the successful material-specific machining based on the feeling machine is presented.